Spatio-Temporal Distribution of Malaria Incidence in Rwandan Highlands - Maniragaba, A.; Simiyu, G. M.; Mwasi, B. N.; Njunwa, J. K. (Africa Environmental Review Journal, 2022)
Malaria remains among the top diseases that are responsible for morbidity and mortality in a big number of developing countries. Efforts are being made to control but it recurs and new incidences are emerging in areas that are known to be malaria free. This study was aimed to investigate distribution of malaria incidence in the highland regions of Karogi, Muhanga and Rubavu districts, Rwanda. Malaria cases for the period ranging from 2004 to 2014 were collected from 26 health centres and incidences were calculated to the standard ration of 1000. Findings indicated less malaria in highland, and it was distributed according to the altitude; high altitude had less malaria incidence while valleys and plains in the highlands were characterised by increased value of malaria incidence. The order of general prevalence in the study area indicated that Muhanga had 9.5/1000, Karongi with 4.39/1000 and Rubavu 1.8/1000. Nyabikenke health centre (Muhanga district) indicated high prevalence 135.5/1000 while Busasamana health centre (Rubavu district) had the lowest prevalence 2.65/1000. The prevalence order was inversely proportional to the altitude. Compared to the national situation, malaria in the highland is still lower, but much effort is needed to control new cases since population may be at the high risk of malaria than other population in endemic areas due to low malaria immunity. Further researches are needed to investigate the cause of malaria incidence in highland for proper mitigation measures.